5=5(x-2)-(x-7)

Simple and best practice solution for 5=5(x-2)-(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5=5(x-2)-(x-7) equation:


Simplifying
5 = 5(x + -2) + -1(x + -7)

Reorder the terms:
5 = 5(-2 + x) + -1(x + -7)
5 = (-2 * 5 + x * 5) + -1(x + -7)
5 = (-10 + 5x) + -1(x + -7)

Reorder the terms:
5 = -10 + 5x + -1(-7 + x)
5 = -10 + 5x + (-7 * -1 + x * -1)
5 = -10 + 5x + (7 + -1x)

Reorder the terms:
5 = -10 + 7 + 5x + -1x

Combine like terms: -10 + 7 = -3
5 = -3 + 5x + -1x

Combine like terms: 5x + -1x = 4x
5 = -3 + 4x

Solving
5 = -3 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
5 + -4x = -3 + 4x + -4x

Combine like terms: 4x + -4x = 0
5 + -4x = -3 + 0
5 + -4x = -3

Add '-5' to each side of the equation.
5 + -5 + -4x = -3 + -5

Combine like terms: 5 + -5 = 0
0 + -4x = -3 + -5
-4x = -3 + -5

Combine like terms: -3 + -5 = -8
-4x = -8

Divide each side by '-4'.
x = 2

Simplifying
x = 2

See similar equations:

| 9x+9+11+11x=180 | | p-3(n-5)=30 | | 2-4-3x=3-4 | | 8e(-e)=10 | | x^2-2mx+m^2-m+1=0 | | -7+7x=-x-8(-2-x) | | 16x^2+64x-48=0 | | Log(9)(X)=1/2 | | ((24x^2)-2c-11)=0 | | Log(32)(X)=1/5 | | (24x^2c-11)=0 | | 5x/24=39 | | F=B(1+rt) | | 7s=5 | | 3x^2+xy-2y^2=o | | 3p^2-pq-2q^2=0 | | 4=3G | | 3x+35=8 | | 3(6x-5)+15x= | | F(x)=x^3-7x^2+24x-18 | | 2*x+0.5x+0.25x+1=100 | | F(x)=x^3+24x^2+7x-18 | | 584000= | | 3n^4-6n^2+9n=0 | | (1)4x+2=5 | | Y=-1x-(4) | | (3x+5)*2x=25 | | x-10=180 | | 3x+5x+2x+5=180 | | (X^2)-2XY=16 | | f(x)=8x^5+4x^4-4 | | 1(2+5x)=5 |

Equations solver categories